2022
DOI: 10.1038/s41598-022-19239-9
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis-mediated disruption in spiral artery remodeling is associated with altered uterine NK cell populations and dysregulated IL-18 and Htra1

Abstract: Impaired spiral artery remodeling (IRSA) underpins the great obstetrical syndromes. We previously demonstrated that intrauterine infection with the periodontal pathogen, Porphyromonas gingivalis, induces IRSA in rats. Since our previous studies only examined the end stage of arterial remodeling, the aim of this study was to identify the impact of P. gingivalis infection on the earlier stages of remodeling. Gestation day (GD) 11 specimens, a transition point between trophoblast-independent remodeling and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Therefore, we sought to determine if AoSMCs could serve as a biologically relevant surrogate for spiral arterial VSMCs since women diagnosed with IRSA exhibit systemic arterial dysfunction during pregnancy that persists after giving birth ( Hermes et al., 2013 ; Veerbeek et al., 2015 ; Harris et al., 2019 ). Moreover, our rat model of P. gingivalis –induced IRSA is created by a chronic oral infection of 3 months duration before breeding ( Tavarna et al., 2020 ; Tavarna et al., 2022 ), which could promote systemic maternal vascular injury. The aorta from sham-inoculated controls and P. gingivalis A7UF-induced IRSA-affected dams were evaluated for vascular injury.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we sought to determine if AoSMCs could serve as a biologically relevant surrogate for spiral arterial VSMCs since women diagnosed with IRSA exhibit systemic arterial dysfunction during pregnancy that persists after giving birth ( Hermes et al., 2013 ; Veerbeek et al., 2015 ; Harris et al., 2019 ). Moreover, our rat model of P. gingivalis –induced IRSA is created by a chronic oral infection of 3 months duration before breeding ( Tavarna et al., 2020 ; Tavarna et al., 2022 ), which could promote systemic maternal vascular injury. The aorta from sham-inoculated controls and P. gingivalis A7UF-induced IRSA-affected dams were evaluated for vascular injury.…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation of our study is that we used one set of bacterial culture conditions that would not reflect the full repertoire of P. gingivalis proteomes that change with the composition of the growth medium ( Veith et al., 2018 ). However, an important caveat of our approach was that it was designed to mimic conditions that we have observed in our in vivo model of infection ( Phillips et al., 2018 ; Tavarna et al., 2020 ; Tavarna et al., 2022 ). Despite the limitations of our proteome study, we identified several P. gingivalis proteins in IRSA-inducing A7UF that had strong, stable interactions with AoSMC proteins that did not occur with non-IRSA-inducing W83.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations